1998
DOI: 10.1107/s0907444997009074
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for the crystallization of soluble proteins using non-ionic surfactants

Abstract: Crystallization trials using three polyoxyethylene surfactants as precipitating agents are described. Of the eight soluble proteins screened, five were successfully crystallized at the first attempt. These included lysozyme, catalase, ferritin, ribonuclease A and ubiquitin. Further work suggested that these surfactants could also be suitable for cryo-crystallographic analysis of crystals. At the concentrations used in the crystallization trials [10-40%(v/v)], they are capable of promoting the formation of non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…One particular class of such additives is surfactants, which are known to bind to proteins in solution, , and in larger quantities, to cause their denaturation . Small amounts of nonionic surfactants may improve the quality of crystals formed from soluble proteins, but under other conditions can cause precipitation by modification of the protein−protein interactions. ,,, We have found that the presence of small quantities of anionic surfactants can drastically modify the morphologies of protein crystalline phases . Both the continuum properties and the molecular mechanisms of surfactant action during protein crystallization are, however, poorly characterized.…”
Section: Introductionmentioning
confidence: 96%
“…One particular class of such additives is surfactants, which are known to bind to proteins in solution, , and in larger quantities, to cause their denaturation . Small amounts of nonionic surfactants may improve the quality of crystals formed from soluble proteins, but under other conditions can cause precipitation by modification of the protein−protein interactions. ,,, We have found that the presence of small quantities of anionic surfactants can drastically modify the morphologies of protein crystalline phases . Both the continuum properties and the molecular mechanisms of surfactant action during protein crystallization are, however, poorly characterized.…”
Section: Introductionmentioning
confidence: 96%
“…Uses of non-ionic surfactants in the cubic phase method shows the crystal growth to be more rapidly at lower pH than higher pH as seen with HEWL crystallization. Crystallization shows few membrane proteins but none of the membrane protein produced crystals which can be suitable for X-ray diffraction in contrast crystals were looks more suitable for soluble proteins (Mustafa et al, 1998). OJBS Science Publications…”
Section: Non-ionic Surfactants Approachmentioning
confidence: 99%
“…As soluble proteins share, to some extent, the aggregation problems of the membrane proteins, the mild nonionic surfactant may also be of use in crystallizing them. A few groups have successfully crystallized soluble proteins with nonionic surfactants (3,4). However, the mechanism of the soluble protein crystallization in the presence of nonionic surfactant is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Variations with C 8 E 4 concentration of parameters obtained from SLS and DLS according to Eqs [1][2][3][4][5]. …”
mentioning
confidence: 99%